Development of a rapid and fruit-saving method for fatty acid composition analysis in olive: a comparative study on 27 cultivars - Rizzo, Marianna; Godino, Gianluca; Perri, Enzo; Zelasco, Samanta; Lombardo, Luca (Frontiers in Plant Science, 2024)
Fatty acid composition is an essential aspect of the qualitative assessment of olive oil. A method for evaluating and trending fatty acid composition of olive varieties directly from a limited amount of drupes, has been proven reliable in comparison with traditional oil analysis. No significant difference was detected between the two methods for the 27 cultivars tested, despite presenting decidedly different acid compositions.The results obtained, crossed with those of oil yield, can represent a useful resource to set the harvest calendars by choosing the most suitable time for the production of superior quality oils and for reducing the risk of pathogen infections or pest attack. For three cultivars, the acid composition was evaluated during three ripening phases (green, veraisoned and veraisoned to black). The different behaviors suggest it is the genotype that determines this -still little known-physiological trait in olive.An interesting finding was that the oils from drupes harvested in August showed linolenic acid values higher than the limit (1.00%) set in the international standards for the classification of olive oils, requesting further investigation.